Randomized, Double-Blinded Clinical Trial for Human Norovirus Inactivation in Oysters by High Hydrostatic Pressure Processing - Leon, Juan S. (American Society for Microbiology, 2011)

(untitled)
Contamination of oysters with human noroviruses (HuNoV) constitutes a human health risk and may lead to severe economic losses in the shellfish industry. There is a need to identify a technology that can inactivate HuNoV in oysters. In this study, we conducted a randomized, double-blinded clinical trial to assess the effect of high hydrostatic pressure processing (HPP) on Norwalk virus (HuNoV genogroup I.1) inactivation in virus-seeded oysters ingested by subjects. Forty-four healthy, positive-secretor adults were divided into three study phases. Subjects in each phase were randomized into control and intervention groups. Subjects received Norwalk virus (8FIIb, 1.0 × 10(4) genomic equivalent copies) in artificially seeded oysters with or without HPP treatment (400 MPa at 25°C, 600 MPa at 6°C, or 400 MPa at 6°C for 5 min). HPP at 600 MPa, but not 400 MPa (at 6° or 25°C), completely inactivated HuNoV in seeded oysters and resulted in no HuNoV infection among these subjects, as determined by reverse transcription-PCR detection of HuNoV RNA in subjects' stool or vomitus samples. Interestingly, a white blood cell (granulocyte) shift was identified in 92% of the infected subjects and was significantly associated with infection (P = 0.0014). In summary, these data suggest that HPP is effective at inactivating HuNoV in contaminated whole oysters and suggest a potential intervention to inactivate infectious HuNoV in oysters for the commercial shellfish industry.